Educational Policy and Girl’s Child Enrollment in Nigeria: Issues, Prospect and Way forward - Yushau, Abubakar S.; Ismaila, Yahaya Aliyu; Usman Rasheed Taiye; Amin , Amin (Medha: A Multidisciplinary Journal, 2026)
Education is the strategy to unlocking many forces rightfully, while Girl-child refer to female child within the range of 6-18 years of age. Overtime, the level of imbalance in the ratio of male to girl child educational enrollment is alarming and has left many questions unanswered. In spite of the human right declaration, free and mandatory government policy on education, and other efforts by both state and foreign donor agencies, girl child education is still dismal in relation to male child educational enrollment in Nigeria. This event has exacerbated a negative impact on girls child; which among includes girls child trafficking, force labour, early marriage, immorality, poverty, among several others. The paper underscores the importance of girl’s child educational enrollment on societal development and nation building. The paper adopts the quantitative data sourcing methods while descriptive survey method was the research methodology. The purposive random sampling method was adopted as the sampling techniques method. The result of the research findings indicates that factors such as culture, religion, poverty, access and inadequacy of schools, and parental negative attitudes are some of the militating factors against girl’s child educational enrollment in Nigeria. The paper recommends that government should provide more girls only schools, cultural eligious reorientation, and vibrant policies on girl chilld education in Nigeria.